Indicators that determine the physical readiness of young judokas aged 13-14 years for fights - Rakhlin, M. A.; Bolotin, A. E.; Vasiliev, I. M.; Martynov, D. I. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify indicators of physical readiness that influence the effectiveness of technical actions and attacking combinations of young judokas aged 13-14 years.